Feeling distressed from making decisions : assessors' need to be right - Chen, Charlene Yijun (2020)
Our research posits that decision-making is particularly distressing for individuals with high assessment tendencies. Assessment involves truth concerns about making the "right" decision. We hypothesize that people with high assessment experience greater distress during decision-making because of their concerns about making a wrong decision. In four studies of chronic assessment conducted across four different decision contexts, we found assessment to be positively associated with distress, with this relation being mediated by concerns with being wrong. A meta-analysis of these results provided support for the robustness of this positive association. Finally, a fifth experimental study that induced assessment found the same association with distress. Moreover, an implicit measure of truth concerns mediated this positive association. Given the prevalence of decision-making activities in everyday life, our findings about how truth concerns can cause distress have important implications for the psychological well-being of assessment-oriented individuals.